Contraception After Surgical and Medical Abortion: A Review. Issue 8 (August 2017) - Roe, Andrea Hsu; Bartz, Deborah
Abstract : Importance: To prevent subsequent unintended pregnancy, contraception should be initiated soon after surgical and medical abortion. Evidence regarding the safety of postabortion contraception, especially for long-acting reversible methods, has accumulated in recent years. Objective: This review seeks to provide up-to-date recommendations about the provision and timing of contraception after surgical and medical abortion. Evidence Acquisition: Recommendations are based on the US Medical Eligibility Criteria (MEC) or on the authors' review of the current literature for topics that the MEC does not address. Results: Contraceptive counseling at the time of abortion should be collaborative. All reversible contraceptive methods are safe to begin immediately after surgical abortion, barring concern for surgical complications or underlying medical contraindications. After medical abortion, the implant may be initiated immediately, combined hormonal contraception may be initiated shortly thereafter, and the intrauterine device may be placed once the abortion is complete. Further research is needed to determine the optimal timing of depot medroxyprogesterone acetate initiation after medical abortion. Conclusions and Relevance: Abortion is an important opportunity for contraceptive counseling and provision. Clinic policies and insurance coverage should maximize access to all contraceptive methods, including long-acting reversible methods. Target Audience: Obstetricians and gynecologists, family physicians. Learning Objectives: After completing this activity, the learner should be better able to describe the importance of combining contraception and abortion provision; specify the contraceptive methods that can be safely offered on the same day as surgical and medical abortion; utilize the MEC to identify medical contraindications to contraceptive use; and recognize the public health benefits of the prompt initiation of long-acting reversible methods.